Corporate personality: a shield to company's members? (2016)
Business entities upon registration by the Registrar of Companies and award of certificates of incorporation thereof, become registered Companies. The issue of a certificate of incorporation incorporates the members of the Company into a persona at law with other attendant consequences. However, the issue of the Status of the Company as a corporate legal personality was not given a clear legal Interpretation until the celebrated English case of SALOMON v. SALOMON CO. LTD. ([1897] A. C. 22; 66) which later became a locus classicus on this subject. It is imperative to note that there are two controversial judgments in this case at the court of first instance and the Court of Appeal respectively before the matter was laid to rest at the House at Lords. This paper seeks to examine some germane issues raised by the House of Lords in this case. Some of the questions bother on whether the principle is essentially to protect members of the Company, the management or employees of the Company against the third party. To what extent can the principle serve as a shield, if it is one? Or is such a protection absolute? Laws are not usually enacted to take retrospective effect, therefore holistic approach should be adopted with a view to properly situate pre-incorporation contract, particularly where the going-concern was previously operating as a ‘business name’ and or ‘registered partnership’.